Extraction of Metal Ions by Interfacially Active Janus Nanoparticles Supported by Wax Colloidosomes Obtained from Pickering Emulsions - Oliver Pauli; Andrei Honciuc (Nanomaterials, 2022)
Most common wastewater treatment technologies for ion extraction and recovery rely on pumping wastewater through ion-exchange columns, filled with surface-functionalized polymer microspheres. To avoid the energetically intensive process of pumping large quantities of water through ion-exchange columns, alternative technologies are being developed, such as water-floating membranes containing ligands. In this context, innovative materials could be deployed. Here, we report nanostructured paraffine wax microspheres capable of floating on water, a design based on Pickering emulsion technology, where Janus nanoparticles act both as emulsion stabilizers and as ligand carriers. In the process of emulsification of molten wax in water, followed by cooling, the branched polyethylenimine (bPEI) carrying Janus nanoparticles are trapped at the molten wax/water interface, forming spherical microspheres or colloidosomes decorated with nanoparticles. The paraffine wax colloidosomes stabilized by ligand-carrying Janus nanoparticles are capable of floating on water and show high metal ion extraction capacities towards Cr(VI), Co(II), Ni(II), Cu(II) and Zn(II). In addition, we demonstrate that the ions can be recovered from the colloidosomes and that the colloidosomes can withstand several extraction/recovery cycles with little or no loss in the absorption capacity.